Cu–Bpin-mediated dimerization of 4,4-dichloro-2-butenoic acid derivatives enables the synthesis of densely functionalized cyclopropanes - Gómez-Roibás, Patricia; Chaves-Pouso, Andrea; Fañanás-Mastral, Martín (Beilstein Journal of Organic Chemistry, 2025)
4,4-Dichloro-2-butenoic acid derivatives are shown to undergo a rare dimerization process when reacted with bis(pinacolato)diboron under copper catalysis. The reaction provides densely functionalized products with excellent levels of chemo-, regio-, and diastereoselectivity. This high degree of functionalization makes these products versatile building blocks for the stereoselective synthesis of chlorocyclopropanes.
Keywords: chlorocyclopropanes; copper; cyclization; 4,4-dichloro-2-butenoic acid derivatives; dimerization